Efektivitas Pendidikan Kesehatan terhadap Pengetahuan Pencegahan COVID 19 pada Anaka Usia Sekolah - Salisa Ashanita Rahmatika; Eka Wisanti; Riau Rosita (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Corona Virus Disease 2019 (COVID-19) is an infectious disease and extremely risky for a group of children. The increased number of COVID-19 incidences among children is a consequence of a relatively low number of Covid-19 examinations among them, while children have more opportunities to play outside the home without any protection of the health protocols. It is necessary to advance children’s knowledge by providing health education using video education. This study aimed to determine the effects of providing COVID-19 prevention health education using video on the school-age children knowledge. This research was a quantitative study with a pre-experimental design using a control group approach. Totally 60 respondents selected by a consecutive sampling technique were invited into the study. Mann Whitney correlation test results revealed a p-value of 0,001, which means that health education using video effectively increased school-age children knowledge about COVID-19 prevention. This findings suggest health services provider to use video education for other children in schools. Video media health education effectively increases children’s knowledge about COVID-19 prevention among school-aged children.